2013
DOI: 10.1136/archdischild-2013-304928
|View full text |Cite
|
Sign up to set email alerts
|

Examining the effects of a targeted noise reduction program in a neonatal intensive care unit

Abstract: The baseline noise in the NICU consistently exceeds guidelines, but reductions in noise levels are achievable. Nonetheless, more work is needed to find the optimal NICU design and noise reduction strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 37 publications
1
25
0
1
Order By: Relevance
“…In a study conducted in Canada, noise measurements during 1 month (pre-intervention) training protocol after the noise measurements for 2 months with alarm system the health personnel and the family was made two months measured by visual stimuli. The weekends were determined to have a quieter environment (p<0.001) and a decrease in noise level (p=0.01) compared to the weekdays (27). In the present study, a significant decrease was detected in the unit in RM with the use of education in addition to normal education (2.09-5.16 dBA).…”
Section: Discussionmentioning
confidence: 39%
See 2 more Smart Citations
“…In a study conducted in Canada, noise measurements during 1 month (pre-intervention) training protocol after the noise measurements for 2 months with alarm system the health personnel and the family was made two months measured by visual stimuli. The weekends were determined to have a quieter environment (p<0.001) and a decrease in noise level (p=0.01) compared to the weekdays (27). In the present study, a significant decrease was detected in the unit in RM with the use of education in addition to normal education (2.09-5.16 dBA).…”
Section: Discussionmentioning
confidence: 39%
“…In the present study, a significant decrease was detected in the unit in RM with the use of education in addition to normal education (2.09-5.16 dBA). Researchers reported that a 3 dB decrease was equivalent to a 50% change in noise levels because the decibel is a logarithmic unit (27). Twenty-fourhour noise measurements, both BE and AE, on Monday, Friday, and Sunday were compared in a study, and about a 3 dB decrease was detected using the education method (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies across the last 10 years have shown that the levels are generally not attainable in a functioning NICU. 16,17 The original bases for existing recommendations included the minimisation of sleep disruption and interference in speech intelligibility among adults. 18 The signal-to-noise ratio of the speech intelligibility assumed a distance of 12 ft (3.7 m) between nurses in an open bay unit (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…12 Many authors on this theme agree that the noise level in the NICU worldwide is still higher than recommended, even checking all the efforts of professionals in minimizing them. 1,[13][14] These data indicate the urgency to carry out educational activities of everyone involved in caring for a further reduction in noise levels in the NICU, and thus preserving the hearing acuity of newborns.…”
Section: Resultsmentioning
confidence: 99%